2014
DOI: 10.1371/journal.pone.0113868
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Needle in the Haystack: The Costs and Cost-Effectiveness of Syphilis Diagnosis and Treatment during Pregnancy to Prevent Congenital Syphilis in Kalomo District of Zambia

Abstract: BackgroundIn March 2012, The Elizabeth Glaser Pediatric AIDS Foundation trained maternal and child health workers in Southern Province of Zambia to use a new rapid syphilis test (RST) during routine antenatal care. A recent study by Bonawitz et al. (2014) evaluated the impact of this roll out in Kalomo District. This paper estimates the costs and cost-effectiveness from the provider's perspective under the actual conditions observed during the first year of the RST roll out.MethodsInformation on materials used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 12 publications
3
57
0
Order By: Relevance
“…In Fortaleza-CE*, half of the interviewed professionals stated that they would request the VDRL for the partner and would only deal with the result 13 . A similar study carried out in Recife-PE* showed a value of 38% for the same index 20 , closer to the one found in Londrina. The data corroborate those pointed out in a similar survey carried in Rio de Janeiro-RJ*, in which approximately 40% of medical professionals and nurses reported having difficulty discussing syphilis with sexual partners 9 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In Fortaleza-CE*, half of the interviewed professionals stated that they would request the VDRL for the partner and would only deal with the result 13 . A similar study carried out in Recife-PE* showed a value of 38% for the same index 20 , closer to the one found in Londrina. The data corroborate those pointed out in a similar survey carried in Rio de Janeiro-RJ*, in which approximately 40% of medical professionals and nurses reported having difficulty discussing syphilis with sexual partners 9 .…”
Section: Discussionsupporting
confidence: 80%
“…Before the training, only 7.8% of the professionals knew this flow, although it had already been in practice for five months. Faced with this reality, it is understood that permanent education actions and changes in the work process must have a planned continuity 18 , because their punctual action informs and updates the professionals, but the change of conduct in practice needs monitoring and correction of errors as learning, not punishment, reinforcing self-analysis and self-management activities of the health teams 19 - 20 . …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for high-risk populations and for individuals with high-risk behaviors, testing in the third trimester is reasonable and becomes cost-effective when seroconversion rates are 19-fold higher than national averages for primary and secondary syphilis [16]. Especially in emerging countries where syphilis is highly prevalent, screening programs regardless of their construct must be coordinated with effective treatment opportunities to be cost-effective [17].…”
Section: Testing For Syphilismentioning
confidence: 99%